Sistem Pendukung Keputusan Pemilihan Supplier Bahan Baku Digital Printing Dengan Metode Additive Ratio Assessment (ARAS) - Imara Gumilar, Nanang; Wahyu Setyaningsih, Putry (CV. Hawari, 2023)
Current developments in technology and business have an impact on human life, especially in the business world operating in the service sector. Business development that is quite rapid is business in the digital printing sector. Godean Digital Printing has quite valuable assets, namely raw material inventory, therefore inventory must be managed well. In production companies which are usually faced with many raw material problems, excess or lack of raw material quality values can disrupt the smoothness of the production process and the quality of the production itself at Godean Digital Printing. So with this, researchers conducted research on determining the supply of production raw materials at Godean Digital Printing. In this study, researchers tried to use the Additive Ratio Assessment method. Additive Ratio Assessment Method. So the researchers took the title